Assessing the Impact of Hermetic Storage Technology on Storage Quantity and Post-Harvest Storage Losses Among Smallholding Maize Farmers in Nepal - Deepak Kumar Nepali; Keshav Lall Maharjan (Agriculture)
Promoting smallholding farmers to use improved storage technology is pivotal to enhance the sustainable agri-food system. Studies suggest that hermetic storage technology reduces post-harvest storage losses, improves grain quality, and enhances food security. However, weak causal evidence is prevalent due to confounding and endogeneity issues in such studies. Hence, this study examines the impact of hermetic storage bags through a randomized encouragement design, using the instrumental variable (IV) approach, among 692 smallholding farmers in Nepal, where maize is one of the major food crops. Farmers were encouraged by offers of 100% and 50% subsidies on the price of up to three Purdue Improved Crop Storage (PICS) bags. We found that an additional unit of the hermetic storage bag increased maize storage by 42.84 kg and reduced post-harvest storage losses by 10 kg (32.92% reduction) for the farmers encouraged with a 100% subsidy. It increased maize storage by 39.2 kg for the farmers encouraged with a 50% subsidy, with no significant effect on post-harvest storage losses in this group compared to the control group. Thus, it is essential to encourage farmers to adopt improved storage technologies to increase storage and reduce post-harvest losses. This can contribute to enhancing local food security.